Effects of parent-provider communication during infant hospitalization in the NICU on parents: A systematic review with meta-synthesis and narrative synthesis. Issue 7 (July 2021) - Labrie, Nanon H.M.; van Veenendaal, Nicole R.; Ludolph, Ramona A.; Ket, Johannes C.F.; van der Schoor, Sophie R.D.; van Kempen, Anne A.M.W.
Highlights: Parent-provider interaction plays a crucial role in family-centered neonatal care. Yet, understanding of the effects of communication on parents was lacking. Meta-synthesis and -analysis of 77 records revealed five main effect groups. Effects can be positive and negative and occur in the short- and (very) long-term. Communication effects have been added to the NICU Communication Framework. Abstract: Objective: To synthesize and analyse the literature on the effects of parent-provider communication during infant hospitalization in the neonatal (intensive) care unit (NICU) on parent-related outcomes. Methods: Systematic review with meta-synthesis and narrative synthesis. Databases (PubMed, PsycINFO, Cochrane Library, CINAHL, Web of Science, Scopus) were searched in October/November 2019. Studies reporting, observing, or measuring parent-related effects of parent-provider communication in the NICU were included. Study quality was assessed using the Quality Assessment Tool for Studies with Diverse Designs. Qualitative studies were meta-synthesized using deductive and inductive thematic analysis. Quantitative studies were analysed using narrative synthesis. Results: 5586 records were identified; 77 were included, reporting on N = 6960 parents, N = 693 providers, and N = 300 NICUs. Analyses revealed five main (positive and negative) effects of parent-provider interaction on parents' (1) coping, (2) knowledge, (3) participation, (4) parenting, and (5) satisfaction . Communication interventions appeared impactful, particularly in reducing parental stress and anxiety. Findings confirm and refine the NICU Communication Framework. Conclusions: Parent-provider communication is a crucial determinant for parental well-being and satisfaction with care, during and following infant hospitalization in the NICU. R. Practice Implications: Providers should particularly consider the impact on parents of their day-to-day interaction – the most occurring form of communication of all.